Decades : a century of fashion - Silver, Cameron; DiLiberto, Rebecca (Bloomsbury, 2012)
Ten chapters, each devoted to the iconic looks of a decade. Includes original designer sketches and patterns and photos of rare couture as styled decades ago and today. Uncover a century of colorful history to inspire the stylish of today for years to come.